NARRATIVE OF NATIONALISM IN MISE-EN-SCENE OF BIOPIC SOEKARNO: INDONESIA MERDEKA - Gunawan, Eric; Wibawarta, Bambang (UI Scholars Hub, 2024)
This paper examines the national narrative presented in the biographical film Soekarno: Indonesia Merdeka (2014). The analysis employs a film studies approach to explore the interplay between visual and narrative strategies within the framework of Eisenstein's theoretical perspectives. Christian Metz's semiotic theory is utilized to decode the signs embedded throughout the film. The study focuses on the visual and narrative strategies employed in the biopic to elucidate the national narrative, particularly through the portrayal of the character Soekarno and his interactions with other key figures. Visual strategies, encompassing cinematography and mise-en-scene techniques, bring to light signs that are intricately linked to national narratives. Simultaneously, the narrative strategy reinforces the coherence of this narrative through pivotal plot points in the film's storyline. In this biopic, audio is construed as an underpinning element that enhances the information and meaning already conveyed through the visuals. The holistic analysis of visual, narrative, and auditory components provides a comprehensive understanding of how the national narrative is constructed and conveyed in Soekarno: Indonesia Merdeka.